Bio-functional hydrogel coated membranes to decrease T-cell exhaustion in manufacturing of CAR T-cells - López Ruiz, Aida; Slaughter, Eric; Bomb, Kartik; Swedzinski, Samantha L.; LeValley, Paige J.; Yun, Zaining; McCoskey, Jacob; Levine, Kara; Steen, Jonathan; Almasian, Joseph; Chatterjee, Aparajita; Carbrello, Christina; et al. (Frontiers in Immunology, 2025)
IntroductionCell therapies have revolutionized cancer treatment, with chimeric antigen receptor (CAR) T-cell therapies at the forefront for the treatment of hematological cancers. However, current manufacturing protocols rely on rapid T-cell activation, which can induce exhaustion and undesirable phenotypes, ultimately reducing the efficacy and persistence of CAR T-cells. Given the importance of T-cell activation as a fundamental step to achieve proliferative phenotypes for cell engineering and expansion, approaches are needed to control activation and increase CAR T-cell quality. To address this need, in this work, we utilized a bioinspired, scalable, tunable platform to direct T-cell activation and decrease exhaustion during CAR T production.MethodsHydrogel-coated membranes (HCMs) were designed with different co-stimulatory ligands and a physiologically-relevant substrate modulus inspired by the native microenvironment in which T cells are programmed. Phenotype, activation, and exhaustion markers were used to compare T cells cultured with HCMs or industry standard TransAct. Next, transduction with a CD19 CAR lentivirus was performed, and the killing potential of the resulting CAR T product was evaluated using an in vitro cytolysis model.ResultsWith this controlled and well-defined system, we hypothesized that a combination of ligands inspired by antigen-presenting cells would promote desired T-cell phenotypes with reduced exhaustion and thereby improved killing efficacy. We found memory phenotypes, minimal exhaustion, and similar activation profiles with HCMs. Additionally, increased T-cell transduction and decreased exhaustion for the CAR T population were observed with HCMs. Further, the killing potential of the resulting CAR T product was evaluated, finding improved in vitro cytolysis of target cells with lower variability with HCMs.DiscussionThese results demonstrate the importance of lower T-cell exhaustion in CAR T manufacturing and present significant opportunities to modulate T-cell phenotypes for cell therapy applications using engineered bioinspired materials that display combinations of co-stimulatory molecules.